Beam to Column Timber Joints with Pretensioned Bolts - Awaludin A.; Hirai T.; Sasaki Y.; Hayashikawa T.; Oikawa A. (Civil Engineering Dimension, 2011)
The effects of pretension in bolts on hysteretic response of timber joints exposed to a bending had been reported by the authors, but the cyclic tests were carried out at small displacement level which might not be applicable for earthquake-resistance design. In this study, similar cyclic tests but at large displacement levels were conducted. Beam to column timber joints with steel side plates were fabricated and continuously loaded until failure. At connection, the bolts were pretension in four different magnitudes: 0 kN, 5 kN, 10 kN and 15 kN. The results showed that frictional action between the steel side plates and wood member as a result of bolt pretensioning significantly increased the (frictional) hysteretic damping and the equivalent viscous damping ratio. It is obvious from the test results that the pretension force in bolts has no influence on the maximum joint resistance but decreases the joint rotational deformation.